The Path From Litter to Soil: Insights Into Soil C Cycling From Long‐Term Input Manipulation and High‐Resolution Mass Spectrometry. Issue 5 (9th May 2018) - Reynolds, Lorien L.; Lajtha, Kate; Bowden, Richard D.; Tfaily, Malak M.; Johnson, Bart R.; Bridgham, Scott D.
Abstract: The path of carbon (C) from plant litter to soil organic matter (SOM) is key to understanding how soil C stocks and microbial decomposition will respond to climate change and whether soil C sinks can be enhanced. Long‐term ecosystem‐scale litter manipulations and molecular characterization of SOM provide a unique opportunity to explore these issues. We incubated soils from a 20‐year litter input experiment for 525 days and asked how litter quantity and source (i.e., roots versus aboveground litter) affected C cycling, microbial function, and the size and molecular composition of C pools. Input exclusion led to a 30% loss of soil C, attributable largely to the nonmineral‐associated C fraction, and to declines in soil C decomposition. The absence of roots caused a shift in the microbial catabolic profile, though there was little evidence that root litter was preferentially stabilized. Although C pool size did not change with litter additions, Fourier transform ion cyclotron resonance mass spectrometry analysis of the finest mineral fraction revealed dramatic changes to the chemical composition of carbon. Lipid content increased proportionally with input addition and was subsequently mineralized during incubation, indicating that this fraction was metabolically active. Moreover, nonmetric dimensional scaling showed that both litter treatments and incubation caused the molecular composition of SOM to change. We conclude that the path of C from litter to soil may involve labile pools and root‐driven microbial activity associated directly with SOM in the soil mineral matrix otherwise previously hypothesized to be stable. Key Points: Twenty years of litter input manipulation caused changes not only in the size but also in the chemical composition of soil C pools Litter exclusion led to a 30% loss of soil C from nonmineral‐associated C Though litter addition did not change C content, there was a change in the chemical composition of the finest mineral‐associated fraction